Pressure distribution model for pressure garments and its verification - Salleh, Mohamed Najib; Acar, M.; Burns, N. D. (2011)
Pressure garments are tight fitting elastic garments which apply pressure to the wounded area of the human body for treatment.The garments are primarily designed to exert pressure on a particular part of the body.Thus, only the correct level of pressure on the wound assists the healing process, therefore it is important to apply the right pressure on the affected part.The pressure distribution model enables a manufacturer or therapist to predict the pressure that the garment applies on the body part without requiring an in-situ pressure measurement.This is a novel, powerful and useful tool. It can also identify the locations that have high or low pressure.